The role of financial technology in improving the financial performance of banks: A field study on a sample of private banks in Erbil governorate (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:               Today, the financial and banking sector is witnessing a qualitative shift thanks to financial technology services, which provide their services to many individuals and companies in quick, easy and less expensive ways compared to traditional means. Financial technology is a new form of financial science that combines financial transactions and technological skills concerned with providing financial services and improving the work environment within Banking institutions, and financial technology provides many advantages such as lower transaction costs, instant payment, and saving more time and effort in conducting banking operations and activities. Banks have taken this into consideration as they are the main engine of countries’ economies and are working to renew their basic structures based on what is required of ways to keep pace with this development. The performance of Drains It has become an urgent necessity to confront the wave of fierce competition imposed by financial technology, which is why banks are racing to possess modern technologicalmeans and provide additional services to their customers, which gives them a competitive advantage in the market.Hence, financial performance in banks is receiving increasing attention because optimal financial performance is the only way to maintain survival and continuity, ensure growth and expansion, and achieve appropriate market value. Financial performance is also one of the basic components of banks, as it provides an integrated system of accurate and reliable information to judge the efficiency of banks. In achieving its objectives effectively and to compare actual performance with pre-determined objectives, through certain indicators expressed in numbers to identify deviations, if any, and identify their causes to work to correct them.